Evaluation of Indigenous Potato Challisha (Solanum tuberosum L. Cv. Challisha) Somaclonals Tolerance to Salinity In Vitro - Md. Sanaullah Biswas; Md. Riazul Islam; Mohammad Zakaria (Journal of Tropical Life Science, 2017)
Potato is one of the most important food crops in the world. It is generally sensitive to salinity and likes to grow in neutral soil. On the other hand, salinity is increasing alarmingly in the ever changing climatic conditions. Thus, the selection of salt tolerant potato cultivars is necessary to keep pace the production of potato. To select salt tolerant cultivars, here we attempt to compare the salinity level between indigenous and modern cultivars. In vitro selection of local and modern potato cultivars were investigated with five levels of NaCl (0, 30, 60, 90 and 120 mM). The indigenous potato Challisha and modern cultivars Diamant and Felsina were used as plant materials. Significant differences were noticed among the cultivars in response to different levels of NaCl. Plant growth and root development were gradually reduced with increased concentration of NaCl. All three cultivars were survived well with exhibiting different growth status up to 60 mM NaCl, but they performed poorly at 120 mM of NaCl. Cultivar Challisha performed better regarding shoot length, root length, the number of nodes per plantlet and the fresh weight per plant up to 90 mM of NaCl. Thus, we can conclude that local indigenous variety Challisha is salt tolerant comparing with the modern cultivated varieties.